2018
DOI: 10.1017/aap.2018.23
|View full text |Cite
|
Sign up to set email alerts
|

The Context and Consequences of Sexual Harassment in Southeastern Archaeology

Abstract: In 2014, the Southeastern Archaeological Conference (SEAC) conducted a sexual harassment survey of its membership. The survey's goal was to investigate whether sexual harassment had occurred among its members, and if so, to document the rate and demographics of harassment. Our findings include a high (66%) level of harassment, primarily among women, with an additional 13% of respondents reporting sexual assault. This article provides an overview of the survey and responses. Additionally, we analyze survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…It is important to note that the NASEM directed these recommendations toward institutional leadership. Other scholars have reported similar recommendations or components of these recommendations as a means to support safe and inclusive field environments in anthropology, as well as other disciplines (Barthelemy et al 2016;Clancy et al 2014;Meyers et al 2018;Nelson et al 2017;St. John et al 2016).…”
Section: Preventing Sexual Harassment and Assault: What We Know From mentioning
confidence: 92%
See 2 more Smart Citations
“…It is important to note that the NASEM directed these recommendations toward institutional leadership. Other scholars have reported similar recommendations or components of these recommendations as a means to support safe and inclusive field environments in anthropology, as well as other disciplines (Barthelemy et al 2016;Clancy et al 2014;Meyers et al 2018;Nelson et al 2017;St. John et al 2016).…”
Section: Preventing Sexual Harassment and Assault: What We Know From mentioning
confidence: 92%
“…conducting research in the southeastern United States, 66% reported sexual harassment and 13% reported sexual assault (Meyers et al 2018). Although not exclusive to field school students, these numbers-and others-suggest that instances of sexual harassment and assault are common and that student trainees are frequently subjected to such treatment (Clancy et al 2014).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…prevalence of both in archaeology (Clancy et al 2014;Meyers et al 2018) and the existence of previous SAA task forces charged with developing strong anti-harassment measures. We quickly identified a clause that required a bylaw referendum to go to a member-wide vote if the petition was endorsed by at least 10% of the SAA, or roughly 800 members.…”
Section: Take Back the Saamentioning
confidence: 99%
“…En esta misma línea, en lo que respecta a la arqueología, el ingreso del feminismo en la década de 1970 generó una serie de cuestionamientos en torno a la realidad que afrontaban y afrontan las mujeres al interior de sus distintas comunidades académicas. En Europa y Estados Unidos se pasó a exponer la necesidad de visibilizar los aportes de las arqueólogas en el avance de la ciencia (Berrocal, 2009, p. 29), la necesidad de democratizar las asignaciones de fondos de investigación (Gero, 1985), el papel determinante que juega la sexualidad en el desarrollo de las carreras académicas (She, 2000;Claasen,2000) y, de forma más reciente, el hostigamiento sexual (Meyers et al, 2018).…”
Section: Comentarios Finalesunclassified